r=qx2+y2
θ=arctan(y/x)
z=z
ˆ
r=cos θˆ
x+sin θˆy
ˆ
θ=−sin θˆ
x+cos θˆy
ˆz=ˆz
dl=drˆ
r+rdθˆ
θ+dzˆz; dτ=rdrdθdz
∇f=∂f
∂rˆ
r+1
r
∂f
∂θ ˆ
θ+∂f
∂zˆz
∇ · v=1
r
∂
∂r(rvr) + 1
r
∂vθ
∂θ +∂vz
∂z
∇ × v=1
r
∂vz
∂θ −∂vθ
∂zˆ
r+∂vr
∂z−∂vz
∂rˆ
θ+1
r∂
∂r(rvθ)−∂vr
∂θ ˆz
∇2f=1
r
∂
∂rr∂f
∂r+1
r2
∂2f
∂θ2+∂2f
∂z2
Identités vectorielles
Triples produits
(1) A·(B×C) = B·(C×A) = C·(A×B)
(2) A×(B×C) = B(A·C)−C(A·B)
Règles du produit
(3) ∇(f g) = f(∇g) + g(∇f)
(4) ∇(A·B) = A×(∇ × B) + B×(∇ × A) + (A· ∇)B+ (B· ∇)A
(5) ∇ · (fA) = f(∇ · A) + A·(∇f)
(6) ∇ · (A×B) = B·(∇ × A)−A·(∇ × B)
(7) ∇ × (fA) = f(∇ × A)−A×(∇f)
(8) ∇ × (A×B) = (B· ∇)A−(A· ∇)B+A(∇ · B)−B(∇ · A)
Dérivées secondes
(9) ∇ · (∇ × A) = 0
(10) ∇ × (∇f) = 0
(11) ∇ × (∇ × A) = ∇(∇ · A)− ∇2A
Théorèmes fondamentaux
Théorème du gradient : Zb
adl· ∇ f=f(b)−f(a)
Théorème de la divergence : ZVdτ(∇ · A) = ISda·A(Green-Ostrogradski)
Théorème du rotationnel : ZSda·(∇ × A) = IPdl·A(Stokes)
2